1996
DOI: 10.1177/0361198196155100101
|View full text |Cite
|
Sign up to set email alerts
|

Development and Benefits of Computer-Aided Travel Time Data Collection

Abstract: Link travel times are one of the most widely used and valuable measurements of congestion. Travel time measures are compatible with multimodal analyses and are understood by nontechnical audiences, yet are rigorous enough for technical analyses by transportation engineers and planners. The “average” car and floating car techniques are the most widely used travel time–based measures. Although there are cost, safety, and data limitation problems associated with collecting travel time data manually, the use of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The test vehicles used in the study were instrumented with a DMI that allows for the collection of speed information at half-second intervals. This technology was successfully demonstrated in previous studies (3,4,(6)(7)(8). Electronic pulses are read from the vehicle's transmission into the DMI, and the subsequent output from the DMI is collected on an on-board laptop computer.…”
Section: Instrumented Test Vehiclesmentioning
confidence: 81%
“…The test vehicles used in the study were instrumented with a DMI that allows for the collection of speed information at half-second intervals. This technology was successfully demonstrated in previous studies (3,4,(6)(7)(8). Electronic pulses are read from the vehicle's transmission into the DMI, and the subsequent output from the DMI is collected on an on-board laptop computer.…”
Section: Instrumented Test Vehiclesmentioning
confidence: 81%
“…The test vehicles used in the study were instrumented with an electronic distance-measuring instrument (DMI). The DMI allows for the collection of speed information at 0.5-s time intervals, and it was demonstrated successfully in previous studies (3)(4)(5). Electronic pulses are read from the vehicle's transmission into the DMI, and the subsequent output from the DMI is collected by an on-board laptop computer.…”
Section: Instrumented Test Vehiclesmentioning
confidence: 94%
“…With improvement computers Distance Measuring Instrument (DMI) came as the solution of Floating car method for measurement of the speed distance using pulses from a sensor attached to the test vehicle's transmission (Quiroga and Bullock, 1998). Turner et al (1998), Benz and Ogden (1996) found limitation in this method relating to installation of the DMI unit and data storage problems. The development of Information Technology and advancement of Global Positioning System (GPS) has largely overcome the data quality and quantity shortcomings of the manual and DMI methods of collecting travel time data and become one of the alternatives to moving car observer method for field data collection.…”
Section: Self Organizing Map Of Artificial Neural Network For Defininmentioning
confidence: 99%